«Nacido con mantillo»: Creencias populares y testimonios literarios acerca del saco amniótico - Hanus, Tamara (Avisos de Viena, 2023)
This article explores the cultural beliefs surrounding the birth with intact membranes, focusing on four literary examples from different cultures: "La Tragicomedia de Calisto y Melibea" (1499) by Fernando de Rojas, "Los tres pelos de oro del diablo" (1819) by the Brothers Grimm, "David Copperfield" (1950) by Charles Dickens, and "The Shining" (1977) by Stephen King. These stories depict the birth of children with intact caul membranes and the various beliefs associated with them, including love, fortune, protection against drowning, and clairvoyance. Despite modern scientific explanations, the cultural significance of caul births continues to be reflected in literature, highlighting the enduring power of superstition and folklore.